Towards Distributed and Interconnected Education: Activism Positioned as a Vehicle for Change - Fauré, Jaime; Contreras-Villalobos, Tabata (Re-presentaciones: Periodismo, comunicación y sociedad, 2022)
The purpose of this brief essay is threefold. First, we will try to summarize the consensus that has been achieved on the existence of a gap between the challenges and challenges posed by the new ecology of learning and the deployment of the current educational system. Secondly, we will delve into a possible general "solution" to this gap, which aims at the creation and implementation of a distributed and interconnected education system. Finally, we will try to make explicit a series of challenges and challenges involved in the creation and implementation of this system from the point of view of politics, here understood in a broad sense that invites to agency action within the different "territories" of the education system. Specifically, we identified three territories to launch situated activism, which are closely linked to each other: (i) laws and public policies; (ii) educational communities; and (iii) educational practices. Our intention is to make it clear that in order to move towards a distributed and interconnected education system it seems essential to act in a politically committed manner in these territories or What is the same, it seems indispensable that we be able to build bridges back and forth between educational institutions and the rest of society.
Keywords: New ecology of learning; Distributed and interconnected education; situated activism; socio-cultural perspective